2022
DOI: 10.3390/pathogens11121441
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Susceptibility of Clinical Gram-Negative and Gram-Positive Bacterial Strains to Fosfomycin and Significance of This Antibiotic in Infection Treatment

Abstract: Multidrug resistance of bacteria has prompted intensive development work on new medicines, but also the search for effective options among the oldest antibiotics. Although intravenous fosfomycin (IVFOS) seems to be an interesting proposal, the recommended agar dilution method for susceptibility determination poses a major problem in routine diagnostic testing. As a consequence, there is a lack of comprehensive data on the frequency of isolation of susceptible or resistant strains. This fact triggered the dispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…As a result, the average diameter of ZIF-8 obtained on surface-functionalized BTO was notably reduced by 52%. We proposed the growth mechanisms of BTO@ZIF-8 to interpret the decreased diameter, and the surface functionalization of BTO accelerated its combination process with ZIF-8, which contributed to the growth termination of ZIF-8 . It is anticipated that BTO@ZIF-8 was embedded into PLA fibers to improve the PM capture capability and enhance the slip effect, lowering the air resistance of PLA/BZ NFMs and also contributing to the promotion of filtration efficiency …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the average diameter of ZIF-8 obtained on surface-functionalized BTO was notably reduced by 52%. We proposed the growth mechanisms of BTO@ZIF-8 to interpret the decreased diameter, and the surface functionalization of BTO accelerated its combination process with ZIF-8, which contributed to the growth termination of ZIF-8 . It is anticipated that BTO@ZIF-8 was embedded into PLA fibers to improve the PM capture capability and enhance the slip effect, lowering the air resistance of PLA/BZ NFMs and also contributing to the promotion of filtration efficiency …”
Section: Results and Discussionmentioning
confidence: 99%
“…We proposed the growth mechanisms of BTO@ZIF-8 to interpret the decreased diameter, and the surface functionalization of BTO accelerated its combination process with ZIF-8, which contributed to the growth termination of ZIF-8. 32 It is anticipated that BTO@ZIF-8 was embedded into PLA fibers to improve the PM capture capability and enhance the slip effect, 33 lowering the air resistance of PLA/BZ NFMs and also contributing to the promotion of filtration efficiency. 25 The energy-dispersive spectrometry (EDS) mapping images showed that both Ba and Ti elements belonging to BTO, along with both Zn and N elements attributed to ZIF-8, were simultaneously determined in BTO@ZIF-8 (Figure 2d,e).…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is mentioned in combination therapy in infections with ESBL-producing strains as an alternative treatment regimen to carbapenems against carbapenemase-producing Gram-negative bacilli, colistin-resistant Gram-negative bacilli, difficult-to-treat P. aeruginosa , or infections with methicillin-resistant staphylococci [ 25 , 26 , 27 , 28 , 29 , 30 ]. High sensitivity to fosfomycin has been demonstrated in many studies, including our own published in 2022 [ 31 ]. At that time, nearly 78% of susceptible strains were found among Enterobacterales and nearly 91% in Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, nearly 78% of susceptible strains were found among Enterobacterales and nearly 91% in Pseudomonas spp. and Staphylococcus strains [ 31 ]. In addition, multi-resistant strains, such as MBL-producing Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Fosfomycin’s unique mechanism of action permits synergy with other antibiotics (carbapenems and aminoglycosides), as has been demonstrated in vitro. Resistance to fosfomycin can develop rapidly when it is used in monotherapy and can be either chromosomal or plasmid-mediated [ 126 ].…”
Section: Other Novel or Repurposed Antibacterial Agentsmentioning
confidence: 99%